Legal aid compliance for poor local community - PURWANTO; CHARLYNA S. PURBA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to learn more about how effective legal aid is for low-income people in the area.Methodology: This research linked law turn variables using the socio-legal method’s interdisciplinary strategy.Findings: The research used a socio-legal approach to conclude that legal aid was not yet very important for the low-income population in the area. Inadequate local legislation that regulates legal aid for low-in comecommunities was identified as a root cause of the problem, as was the widespread belief that legal aid authority lies squarely within the purview of the central government. Legal aid for the poor in a community works best when it is coordinated between the federal government and local authorities (in this case, a local vertical official).Implications/Novelty: The Ministry of Justice and Human Rights and the Local Government need to improve their coordination and synergy to maximize the delivery of legal aid to the poor in their communities.